2020
DOI: 10.1186/s12974-020-01768-7
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl itaconate, an itaconate derivative, exhibits immunomodulatory effects on neuroinflammation in experimental autoimmune encephalomyelitis

Abstract: Background: Inflammatory stimuli induce immunoresponsive gene 1 (IRG1) expression that in turn catalyzes the production of itaconate from the tricarboxylic acid cycle. Itaconate has recently emerged as a regulator of immune cell functions, especially in macrophages. Studies show that itaconate is required for the activation of anti-inflammatory transcription factor Nrf2 by LPS in mouse and human macrophages, and LPS-activated IRG1-/macrophages that lack endogenous itaconate production exhibit augmented inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 51 publications
(60 reference statements)
1
56
1
Order By: Relevance
“…Indeed, through its immunomodulatory and anti-inflammatory properties, DMI reduces peripheral Th1/Th17 differentiation and CNS infiltration and exerts a protective effect in the EAE mouse model of MS. Moreover, on primary microglia, DMI lowers LPS-induced activation and inflammatory cytokine production [162].…”
Section: Potential Dmf Alternatives: Emerging Anti-inflammatory and Amentioning
confidence: 94%
“…Indeed, through its immunomodulatory and anti-inflammatory properties, DMI reduces peripheral Th1/Th17 differentiation and CNS infiltration and exerts a protective effect in the EAE mouse model of MS. Moreover, on primary microglia, DMI lowers LPS-induced activation and inflammatory cytokine production [162].…”
Section: Potential Dmf Alternatives: Emerging Anti-inflammatory and Amentioning
confidence: 94%
“…Moreover, DMI was shown to offer a protection against myocardial and cerebral ischemic/reperfusion injury in animal models (10,11). Finally, DMI was recently reported by our group to suppress neuroin ammation and ameliorate disease severity in experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (12).…”
Section: Introductionmentioning
confidence: 92%
“…Presently, the immunomodulatory effects of IRG1/itaconate axis were mainly evaluated in the peripheral in ammatory immune responses. Although we have recently reported that DMI, an itaconate derivative, suppressed neuroin ammation and ameliorated disease severity in the chronic CNS disease, EAE (12), whether IRG1/itaconate axis modulates the acute CNS disease, ischemic stroke, remains unexplored. Hence, in this study we investigated the potential immunomodulatory effects of IRG1 on the alleviation of ischemic brain injury and elucidated the molecular mechanisms underlying the protective effect of IRG1 in ischemic stroke.…”
Section: Irg1 De Ciency Represses Bdnf Expression In the Ischemic Bramentioning
confidence: 99%
“…The DON-mediated ALI resolution also involves the Amphiregulin (Arg) generation. The dimethyl itaconate (DMI, an itaconate derivative) treatment inhibits the pro-inflammatory brain macrophages (microglia), Th1/Th17 differentiation, and neutrophil infiltration in the brain to decrease the neuroinflammation [257]. Thus DMI has the potential to use in severe COVID-19 patients with ALI/ARDS as the lung damage observed involves infiltration and overactivation of macrophages, Th1, and Th17 cells.…”
Section: Targeting Immune Cell Metabolism During Severe Covid-19mentioning
confidence: 99%